2013
DOI: 10.1007/s10530-013-0577-x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance of the invasive tree Ligustrum lucidum in a subtropical dry forest: does habitat fragmentation boost or limit invasion?

Abstract: The spread of non-native invasive plants is closely linked to land use changes imposed by human activities such as the expansion of urbanizations and agricultural activities that result in the loss and fragmentation of native forests. While the conditions generated in fragmented forests may provide suitable new habitat for the arrival and establishment of invasive plant propagules, we know little about the reproductive performance of established invasive populations growing in fragmented conditions. We assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 63 publications
(120 reference statements)
0
18
0
Order By: Relevance
“…1 Percentage of studies about L. lucidum invasion carried out in each continent tubular in shape to 1.5 mm long, with lobes that are 2-4 mm long. The flowers are hermaphrodite and pollinated by insects Aguirre-Acosta et al 2014). The inflorescences are 100-250 mm long, 200 mm wide, and are broadly pyramid-to cone-shaped.…”
Section: A-taxonomy and Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…1 Percentage of studies about L. lucidum invasion carried out in each continent tubular in shape to 1.5 mm long, with lobes that are 2-4 mm long. The flowers are hermaphrodite and pollinated by insects Aguirre-Acosta et al 2014). The inflorescences are 100-250 mm long, 200 mm wide, and are broadly pyramid-to cone-shaped.…”
Section: A-taxonomy and Morphologymentioning
confidence: 99%
“…In the introduced area, L. lucidum was widely planted for hedge, shade, shelter and probably garden purposes because it is an attractive tree that gives good shade, grows rapidly and it produces fragrant flowers (Johnson 1953 ; Johnson 2009 ; Hoyos et al 2010 ; Aguirre-Acosta et al 2014 ; Hummel et al 2014 ; Rodrigues et al 2015 ). A study performed in New Zealand found that L. lucidum has a good wood for barbecue charcoal producing persistent heat (Wilcox 2000 ).…”
Section: The Speciesmentioning
confidence: 99%
“…Alterations in species composition and community structure may change the availability of environmental resources for alien plants. Changes in land use types and forest management regimes may also bring alien propagules to the resident community, raising possibilities of alien plant invasion [65]. Our study has identified indicators for habitat and community invasibility; however, further work such as control experiments still needs to be done to enhance our mechanistic understanding of the interactions between plant invasion and the biotic and abiotic indicators of habitat invasibility.…”
Section: Discussionmentioning
confidence: 92%
“…Under park maintenance of either moderate or perfect intensity, seed density did not correlate with tree circumference. Lack of correlation can be caused either by habitat effects on seed production of honey locust specimens, as it has already been described for other species (Rocha and Aguilar 2001;Aguirre-Acosta et al 2014), or by the park maintenance itself. The latter seems to be the more obvious reason because in neglected parks, where more or less natural accumulation of soil seed bank could take place, significantly higher seed density was observed under big trees than under small ones, and also in the direct correlation between tree circumference and seed density we obtained positive and significant relationship in a linear regression test.…”
Section: Discussionmentioning
confidence: 94%
“…Increasing density of soil seed bank under the canopy of woody species parallel with the age of the specimens is a plausible assumption, although rarely documented by published studies (but see Allen et al 1995;Cseresnyés and Csontos 2012;Aguirre-Acosta et al 2014). The accumulation of seed bank should be more pronounced for trees known about considerable survival of their seeds, retaining germinability for long periods in the soil, like the case of honey locust (Ferreras et al 2015).…”
Section: Discussionmentioning
confidence: 99%